2000
DOI: 10.1002/(sici)1526-968x(200003)26:3<174::aid-gene2>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent expression of turtleDmrt1 prior to sexual differentiation

Abstract: Summary: Vertebrates employ varied strategies, both chromosomal and nonchromosomal, to determine the sex of the developing embryo. Among reptiles, temperature‐dependent sex determination (TSD) is common. The temperature of incubation during a critical period preceding sexual differentiation determines the future sex of the embryo, presumably by altering the activity or expression of a temperature‐dependent regulatory factor(s). Here we examine the expression of the Dmrt1 gene, a candidate regulator of mammalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(23 citation statements)
references
References 21 publications
(23 reference statements)
1
22
0
Order By: Relevance
“…However, it is interesting to note that, in larvae reared at FPT, dmrt1 expression remained low throughout the experiment (See Additional file 1: Table S1), which opens the question on the function of dmrt1 in ovarian development in pejerrey [76]. Similar results have been reported in reptiles with TSD [30,77-79]. …”
Section: Reviewsupporting
confidence: 63%
“…However, it is interesting to note that, in larvae reared at FPT, dmrt1 expression remained low throughout the experiment (See Additional file 1: Table S1), which opens the question on the function of dmrt1 in ovarian development in pejerrey [76]. Similar results have been reported in reptiles with TSD [30,77-79]. …”
Section: Reviewsupporting
confidence: 63%
“…In humans, DMRT1 maps to the short arm of chromosome 9, and hemizygous deletion of this region is associated with defective testicular development (6,7). Dmrt1 has also been isolated in fish (8)(9)(10)(11)(12)(13), amphibians (14), reptiles (15), and marsupials (16), and Dmrt1 expression pattern in these species is consistent with a role in testis differentiation.…”
mentioning
confidence: 79%
“…In the temperature-dependent sex determination of alligators and turtles, DMRT1 exhibits the expected expression pattern for a sex-determining gene (19,33). In rainbow trout it has been shown that DMRT1 is expressed in the developing male gonad before morphological differentiation (15).…”
Section: Discussionmentioning
confidence: 99%